Biological activities of four Melicope species - Mohd Hashim, Najihah; Rahmani, Mawardi; Mohd Ismail, Hazar Bebe; Md. Sukari, Mohd. Aspollah; Ali, Abdul Manaf; Ee, Gwendoline Cheng Lian (Universiti Kebangsaan Malaysia, 2009)
The leaves and stem barks extracts of four plant species, Melicope confusa, M. clemensiae, M. lunu-ankenda and M. latifolia were screened for their antimicrobial, antioxidant and cytotoxic activities. Almost all extracts of M. clemensia exhibited moderate growth inhibition when tested against the three pathogenic fungi. However, when tested against pathogenic bacteria, the three leaves extracts showed strong activity against methicillin resistant S. aureus and moderate for the other bacteria. In the antioxidant assay by using DPPH, the three leaves extracts of M. lunu-ankenda exhibited significant activity with with IC50 values of 7.8, 15.6 and 7.8 μg/mL. In addition, the petroleum ether leaves extract of M. clemensiae and the chloroform leaves extract of M. lunu-ankenda showed strong cytotoxic activity when tested against human promyelocytic leukemia (HL60) cell line with IC50 values of 2.8 and 0.8 μg/mL, respectively.